2017
DOI: 10.1186/s12940-017-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

Residential distance to major roadways and cardiac structure in African Americans: cross-sectional results from the Jackson Heart Study

Abstract: BackgroundHeart failure (HF) is a significant source of morbidity and mortality among African Americans. Ambient air pollution, including from traffic, is associated with HF, but the mechanisms remain unknown. The objectives of this study were to estimate the cross-sectional associations between residential distance to major roadways with markers of cardiac structure: left ventricular (LV) mass index, LV end-diastolic diameter, LV end-systolic diameter, and LV hypertrophy among African Americans.MethodsWe stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 48 publications
0
7
1
Order By: Relevance
“…Intriguingly, they reported a small increase in pulmonary artery systolic pressure in those living 300 to 999 meters from major roads (compared with those who lived ≥1000 meters)—a finding which may explain the mechanism of RV dilatation in relation to the distance to major roads observed in our study. A follow-up study in the same JHS cohort found a 1.2-mm larger LV end-systolic diameter in participants residing <150 meters from a major road in comparison with those living ≥1000 meters), although no association was detected between indexed LV mass and proximity to major roads 40…”
Section: Discussionmentioning
confidence: 92%
“…Intriguingly, they reported a small increase in pulmonary artery systolic pressure in those living 300 to 999 meters from major roads (compared with those who lived ≥1000 meters)—a finding which may explain the mechanism of RV dilatation in relation to the distance to major roads observed in our study. A follow-up study in the same JHS cohort found a 1.2-mm larger LV end-systolic diameter in participants residing <150 meters from a major road in comparison with those living ≥1000 meters), although no association was detected between indexed LV mass and proximity to major roads 40…”
Section: Discussionmentioning
confidence: 92%
“…Descriptive statistics provide an overview of study population characteristics, residential exposure characteristics and geometric mean HCC concentration with 95% confidence interval. Air pollution variables were logarithmically transformed (ln-scale) because of skewed distributions, distance to major roads was logarithmically transformed to reflect the non-linear distance decay of traffic-related exposure to air pollutants [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…Van Hee et al revealed that living within 50 meters of a major roadway is significantly associated with higher left ventricular (LV) mass index but not with ejection fraction (EF) in the MESA Air cohort [70]. Susceptibility for subclinical systolic dysfunction among African Americans was confirmed in the Jackson Heart Study where living near roads was associated with LV end-systolic diameter [89]. Racial/ethnic minority groups, especially blacks, had a higher risk for adverse clinical cardiovascular outcomes due to air pollution compared to non-Hispanic whites in California [90].…”
Section: Sociodemographics (Age Sex Racial/ethnic Minorities and Lomentioning
confidence: 99%